Sosialisasi Motivasi, Peningkatan Jiwa Kewirausahaan Secara Teknologi yang Digunakan Para Pekerja untuk Meningkatkan Daya Saing - Selvi Yona Sari; Desi Permata Sari; Della Asmaria Putri (Majalah Ilmiah UPI YPTK, 2021)
The Central Statistics Agency provides data which states that the unemployment rate in Indonesia in 2021 is very high. Every year unemployment remains a problem that must be solved. One solution is to provide job opportunities by increasing the entrepreneurial spirit by establishing small businesses (MSMEs). Padang is a city rich in the potential of MSMEs of wood-based artisans and the potential of wood natural resources. Wood is a material that has many advantages and has many benefits. Therefore, the motivation to improve the entrepreneurial spirit needs to be increased. As well as participants are expected to be able to have the ability to manage technology in the face of increased competitiveness. This socialization activity aims to provide motivation about entrepreneurship and can benefit from the potential that exists and can be applied to MSMEs Hobby Kayu in the city of Padang. Technology capabilities can increase the income of the Hobby Kayu MSME community in padang city. Socialization is given to 20 employees of UMKM Hobby Kayu. The results of socialization show the increasing entrepreneurial spirit in developing MSMEs Hobby Kayu in the city of Padang. To increase competitiveness, it takes training and technological skills to hone the skills they have.